2015
DOI: 10.1080/03650340.2015.1024665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated management on Fusarium wilt progression and grain yield of chickpea in Syria

Abstract: Fusarium wilt, caused by Fusarium oxysporum Schlechtend.: f. sp. ciceris (Padwick) Matuo & K. Sato, is a major production problem in many countries. A study was conducted to develop an integrated management of Fusarium wilt of chickpea using genotypes, sowing dates (January as early sowing and March/April as spring sowing) and fungicide seed treatments under natural infested plots in research plots and farmers' fields 2007-2009 cropping seasons. In most cases, sowing date and fungicides did not affect disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Many studies showed that Fusarium wilt development on chickpea is favored by spring (March) planting compared with winter planting (November and December) [16]. The integration of January sowing with partially resistant cultivars decreased fusarium wilt incidence and increased seed yield [20]. In Spain, Navas-Cortés et al [25] demonstrated that advancing chickpea planting from early spring to early winter can decrease Fusarium wilt epidemics and increase seed yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies showed that Fusarium wilt development on chickpea is favored by spring (March) planting compared with winter planting (November and December) [16]. The integration of January sowing with partially resistant cultivars decreased fusarium wilt incidence and increased seed yield [20]. In Spain, Navas-Cortés et al [25] demonstrated that advancing chickpea planting from early spring to early winter can decrease Fusarium wilt epidemics and increase seed yield.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the appearance of Foc races and other root rot disease complexes affecting chickpeas, integrating different disease management options is recommended [19,20]. The objective of this study was to determine the effect of integrating chickpea genotypes with sowing dates on Fusarium wilt development and the yields of chickpeas.…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends were observed for interaction effects of varieties × sowing dates on incidence, AUDPC, and the disease progress rate at both locations. Likewise, Yigrem et al ( 2018), Kemal et al (2015), and Biswas & Ali (2017) confirmed strong influence of varieties and sowing dates on disease parameters.…”
Section: Discussionmentioning
confidence: 79%
“…To determine the efficacy of variable sowing dates (as there was a significant difference between early and late sowing dates) on grain yield, percent grain yield reduction due to early sowing was determined using the formula suggested by Kemal et al. (2015): Grainyieldreduction()%badbreak=0.28emEarlysowingLatesowingEarly0.28emsowing0.28emgoodbreak×0.28em100,$$\begin{equation*}{\mathrm{Grain\;yield\;reduction\;\;}}\left( {\mathrm{\% }} \right) = {\mathrm{\;}}\frac{{{\mathrm{Early\;sowing}} - {\mathrm{Late\;sowing}}}}{{{\mathrm{Early\;sowing}}}}{\mathrm{\;}} \times {\mathrm{\;}}100,\end{equation*}$$…”
Section: Methodsmentioning
confidence: 99%
“…Generally the recommended control practices for F. oxysporum include use of resistant varieties, fungicidal seed treatments, adjustment of planting dates, use of biofumigants, bioagents and crop rotation techniques among others (Blanca et al, 2004;Ajiloba and Babalola 2013;and Kemal et al, 2015). In Kenya, farmers grow the crop during the short rainy season when the disease pressure is low.…”
Section: Introductionmentioning
confidence: 99%